2022
DOI: 10.2337/dc21-1841
|View full text |Cite
|
Sign up to set email alerts
|

A Machine Learning–Based Predictive Model to Identify Patients Who Failed to Attend a Follow-up Visit for Diabetes Care After Recommendations From a National Screening Program

Abstract: OBJECTIVE Reportedly, two-thirds of the patients who were positive for diabetes during screening failed to attend a follow-up visit for diabetes care in Japan. We aimed to develop a machine-learning model for predicting people’s failure to attend a follow-up visit. RESEARCH DESIGN AND METHODS We conducted a retrospective cohort study of adults with newly screened diabetes at a national screening program using a large Japanese… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 20 publications
2
6
0
Order By: Relevance
“…Adherence to follow-up visits among those who were required to have them varied depending on the type of screening. Adherence was higher for cancer screenings than for diabetes, hypertension, or dyslipidemia screenings, which is consistent with previous reports (11) , (14) , (15) , (16) . Adherence improved for some cancer screenings, as well as for diabetes, hypertension, and dyslipidemia screenings in 2021, suggesting that those who underwent screenings in 2021 were more likely to have higher health literacy.…”
Section: Discussionsupporting
confidence: 92%
“…Adherence to follow-up visits among those who were required to have them varied depending on the type of screening. Adherence was higher for cancer screenings than for diabetes, hypertension, or dyslipidemia screenings, which is consistent with previous reports (11) , (14) , (15) , (16) . Adherence improved for some cancer screenings, as well as for diabetes, hypertension, and dyslipidemia screenings in 2021, suggesting that those who underwent screenings in 2021 were more likely to have higher health literacy.…”
Section: Discussionsupporting
confidence: 92%
“…The positive association between the HbA1c levels at the health checkup and the clinic visits in the present study was also reported by Tsujimura et al 10 . and Okada et al ., 13 whereas the influence of HbA1c level on the subsequent clinic visit rates hit a low value ceiling and was <30% even for HbA1c ≥8.0%. We added further evidence that previous health checkup results can affect the subsequent clinic visit.…”
Section: Discussionsupporting
confidence: 91%
“…Tsujimura et al included glucose measurement in their definition of clinic visit, and we did not. Recently, Okada et al 13 showed that fewer physician visits in the previous year, lower HbA1c levels and no history of antidyslipidemic or antihypertensive treatment were associated with fewer clinic visits. They included the presence/absence of hyperglycemia in the health checkups a year before as a variable in their candidate predictors; however, the Lasso regression estimating the proportion of follow-up clinic visits did not choose the variable in the final model.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations